FENOMENA MARAKNYA PEER TO PEER LENDING DI MASA PANDEMI COVID-19: MITIGASI RISIKO HUKUM BAGI PEMINJAM [The Phenomenon of Peer-to-Peer Lending During the Covid-19 Pandemic: Mitigation of Legal Risks for Borrowers] - Jerry Shalmont; Dora Dominica (Law Review, 2022)
The use of Peer to Peer Lending (P2P Lending) has been increasing rapidly since the Covid-19 pandemic in Indonesia, online loan has become a financing option for individuals and business entities. However, the facts showed that some P2P Lending providers operate without proper licenses from the Financial Services Authority (OJK), resulting in huge disadvantages for the borrowers as a result of illegal P2P Lending. This paper will analyze the legal aspects of P2P Lending in terms of risks, from its legality to supervision, and the role of associations in building a sustainable fintech ecosystem. Legal risks should be differentiated from investment risks in which from the user side, especially the borrowers, it is important to act proactively to check whether P2P Lending providers are legal and registered with OJK for risk management. This paper uses normative research by referring to some P2P Lending prevailing laws and regulations in Indonesia as well as factual facts. There are two types of approaches used, namely the statute and conceptual approach, to obtain the desired research results.Bahasa Indonesia Abstrak: Penggunaan Peer to Peer Lending (P2P Lending) sangat berkembang pesat sejak pandemi Covid-19 di Indonesia, pinjaman online menjadi salah satu opsi pembiayaan baik bagi individu sampai dengan badan usaha. Akan tetapi, fakta menunjukan bahwa cukup banyak penyelenggara P2P Lending yang beroperasi namun tidak memiliki izin resmi dari Otoritas Jasa Keuangan (OJK), yang pada akhirnya mengakibatkan banyak pengguna yang merasa dirugikan akibat P2P Lending ilegal. Tulisan ini akan menganalisis aspek hukum dari P2P Lending dari segi risiko, legalitas sampai dengan pengawasan, serta peranan asosiasi dalam membangun ekosistem fintech yang berkelanjutan. Risiko hukum harus dibedakan dari risiko investasi dari sisi pengguna terutama peminjam, sangatlah penting untuk berperan proaktif mencari tahu penyelenggara P2P Lending legal dan terdaftar di OJK dalam rangka manajemen risiko. Jurnal ini menggunakan penelitian normatif dengan mengacu pada ketentuan hukum dan peraturan P2P Lending yang berlaku di Indonesia. Ada dua jenis pendekatan yang digunakan yaitu pendekatan undang-undang dan konseptual, guna mendapatkan hasil penelitian yang diinginkan.